A new species of the mygalomorph spider genus Euagrus Ausserer (Araneae: Euagridae) from central Mexico and new records of E. gus Coyle from Tlaxcala - Valdez-Mondragón, Alejandro; Velasco, Héctor Vicente Salinas; Bueno-Villegas, Julián (Zootaxa, 2026)
A new species of the spider genus Euagrus Ausserer, 1875 from temperate pine-oak forests in the states of Tlaxcala and Hidalgo, Mexico is described: E. pulque sp. nov. The description of the new species is based on male and female adult specimens. Additionally, Euagrus gus Coyle, 1988 is recorded for the very first time in the state of Tlaxcala. These species have sympatric distributions in La Malinche National Park, Tlaxcala. With this description, the diversity of the genus increases to 23 species, with Mexico harboring the highest diversity with 17 described species.